Failure Characteristics of Anchorage Structure After Cylindrical Reaming - Liu, Aolong (International Journal of Natural Resources and Environmental Studies, 2026)
To reveal the failure mechanism of anchorage systems with cylindrical reaming and clarify the internal correlation among anchorage failure, surrounding rock stress, and anchorage agent displacement, a three-dimensional integrated model of the surrounding rock-bolt-anchoring agent-reaming section was established using the Abaqus numerical simulation method based on the cylindrical reaming anchorage engineering in deep soft rock roadways. Seven groups of working conditions with different reaming diameters were designed. Combined with visual analysis of surrounding rock stress and anchorage agent displacement nephograms, as well as theoretical calculations, the failure characteristics, types, and evolution laws of the anchorage structure after reaming were systematically studied. The results show that anchorage failure in cylindrical reaming is dominated by damage to the anchoring agent, which manifests in three core forms: interfacial debonding, plastic rheology, and fracture. An unreasonable reaming diameter causes significant stress concentration at the junction of the reaming section and the reference borehole, and the degree of stress concentration has a nonlinear relationship with the reaming diameter, which is the core inducement of anchorage failure. The displacement and deformation of the anchoring agent increase with the deviation of the reaming diameter from the optimal value, and the deformation concentration area is highly coincident with the stress concentration area, which directly determines the type and degree of anchorage failure. The optimal reaming diameter is 40 mm. Under this condition, the surrounding rock stress is uniformly distributed, the displacement and deformation of the anchoring agent are the smallest, and the risk of anchorage failure is the lowest. The research results provide an intuitive theoretical basis for parameter optimization and failure prevention and control of cylindrical reaming anchorage technology.